Reproductive health challenges among women in internally displaced camps in Benue State: a protocol for a community-based health education interventional study. (2023)
Sexual and reproductive health (SRH) services are a necessity for marginalized persons such as the displaced. The protocol describes an intervention that can contribute to overcoming challenges associated with SRH service delivery of three selected reproductive health (RH) services: HIV/AIDS, contraception, and cervical cancer screening. A pre-and post-intervention approach will be used to evaluate the effect of an intervention with trained Community-Based Reproductive Health Personnel (CBRHP) and/or mHealth technology within the selected IDP camps. Three (3) months of health education through the CBRHP and/or via mHealth technology will be provided. Using a questionnaire, interviews, and Focus Group Discussion (FGD) guide, the researcher will assess the suitability of this intervention to attain the objectives. Data analysis will be done with SPSS version 26. Univariate analysis will include mean and standard deviation, bivariate analysis will include a chi-square test of goodness for the association of variables, and McNemer’s test to evaluate the effect of the intervention by comparing consistency in response across the variables under study. Multivariate analysis will be used to assess if sociodemographic, knowledge and health service impacts access and use of RH services. For qualitative analysis, findings will be grouped into themes. The outcomes of each theme will be used to complement the findings of the quantitative analysis. The primary outcome measures will include the level of knowledge of SRH, the number of people who want to access RH services and which RH services are most sought by the respondents. If the use of CBRHP is successful, there will be an increase in knowledge and use of HIV/AIDS, contraception and cervical cancer services. Challenges associated with access and uptake of RH services will also be assessed. (Afr J Reprod Health 2023; 27 [10]: 133-144).